Bangkrut dalam al-Quran; Studi Tematis Pemahaman Kata Khasara dalam Al-Qur’an - Syarif Hidayat (STAI Terpadu Yogyakarta, 2022)
This paper examines how Bankruptcy in the Qur'an. Understanding is obtained through the meaning of the word Khasara in the Qur'an. This study uses library research, and uses an approach to the interpretation of the Qur'an in terms of thematic interpretation. The method used in the discussion of this paper is qualitative, this method is used to find the desired meaning of the word Khahara, the existing data is processed for further interpretation into concepts that can support the objectives and objects of discussion. After searching the meaning of the word khashara, an understanding is obtained that the bankruptcy described in the Qur'an includes several circumstances; First, do not follow the rules, do things that can break the order, tend to be arbitrary, Second, follow things that are generally inappropriate or should not be followed, Third, people who betray or violate the agreement, Fourth, orders us to fair or fair and do not commit fraud, Fifth, focus on one thing that is not in principle and neglect other things that are more important